Alkyl Bridge Length to Bias the Kinetics and Stability of Consecutive Supramolecular Polymerizations. Issue 2 (26th November 2019) - Greciano, Elisa E.; Alsina, Silvia; Ghosh, Goutam; Fernández, Gustavo; Sánchez, Luis
Abstract: Herein, the impact of alkyl bridge length is unraveled on the self‐assembly of N ‐annulated perylenetetracarboxamides 1–4 that cooperatively form supramolecular polymers. Spectroscopic studies in different solvents as media for the self‐assembly demonstrate the impact that the length of the bridge separating the two amide groups of compounds 1–4 exerts on the supramolecular polymerization process: i) in MCH/Tol (8/2), compounds 1–3 exhibit a consecutive process that, however, it is not operative for 4 ; ii) the presence of three methylene units in 2, which can induce a parallel distribution of the amide groups, notably decreases the stability of the corresponding aggregates in Tol; iii) increasing the spacer length accelerates the conversion of the metastable, intramolecularly H‐bonded monomeric species, which prevents to develop seeded supramolecular polymerizations; iv) the presence of a spacer with five methylene units in 4 hinders the formation of the corresponding 10‐membered pseudo‐cycle; and v) only the higher relative stability of the inactivated monomeric species of 1 enables pathway complexity, with a kinetically controlled self‐assembly to yield nanoparticles and a thermodynamically controlled supramolecular polymerization to achieve fibrillar structures. The results presented herein expand the knowledge on the structure/property relationship for self‐assembling units to provide pathway complexity and to bias the kinetics and stability of the supramolecular aggregates. Abstract : The impact of the alkyl bridge length in the supramolecular polymerization of N ‐annulated perylenes is unraveled. This alkyl bridge separating the two amide groups strongly conditions the stability of both the metastable monomeric species and the final aggregates. A strong impact on the different pathway complexity is also disentangled.